Formulation and Evaluation of Mucoadhesive Tablets of Niacin using Different Bioadhesive Polymers - GAJANANV.SHINDE; S.SUDHARSHINI; B.STEPHENRATHINARAJ; CH.RAJVEER; D.KUMARASWAMY; GANESH S. BANGALE (International Journal of Pharma and Bio Sciences, 2010)
In the present study, to establish mucoadhesive tablets of niacin using different bioadhesive polymers. The tablets were prepared using Sodium Carboxy methyl cellulose (SCMC), carbopol940P and Hydroxy Propyl Methyl Cellulose (HPMC K4M) as bioadhesive polymers to impart mucoadhesion. Tablets were evaluated by different parameters such as weight uniformity, content uniformity, thickness, hardness, surface pH, swelling index, ex vivo mucoadhesive strength, in vitro drug release, and in vitro drug permeation. . The present study concludes that mucoadhesive tablets of niacin can be a good way to swelling and bioadhesion properties a good improve the bio availability of niacin.